2023
DOI: 10.1021/acsomega.2c06791
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensors Based on a Composite of Electrochemically Reduced Graphene Oxide and PEDOT:PSS for Hydrazine Detection

Abstract: In this study, hydrazine sensors were developed from a composite of electrochemically reduced graphene oxide (ErGO) and poly (3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), deposited onto a glassy carbon electrode (GCE). The structural properties, electrochemical characterization, and surface morphologies of this hydrazine sensor were characterized by Raman spectroscopy, Fourier transform infrared (FTIR) spectroscopy, electrochemical impedance spectroscopy (EIS), and scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…The PVP stabilized the aggregation of cf Moreover, the presence of O and N in PVP extended the affinity of these particles to interact with graphite-layered particles. CF nanoparticles did not wholly block the sight of conductive graphite, as pseudocapacitive behaviour was observed in the CV of the CG/G electrode [25]. Furthermore, the dispersed CF nanoparticles provided nucleation sites for the growth of PANI on the surface of graphite.…”
Section: Mechanismmentioning
confidence: 96%
“…The PVP stabilized the aggregation of cf Moreover, the presence of O and N in PVP extended the affinity of these particles to interact with graphite-layered particles. CF nanoparticles did not wholly block the sight of conductive graphite, as pseudocapacitive behaviour was observed in the CV of the CG/G electrode [25]. Furthermore, the dispersed CF nanoparticles provided nucleation sites for the growth of PANI on the surface of graphite.…”
Section: Mechanismmentioning
confidence: 96%
“…These features enable graphene to strongly adsorb target ions, increase surface concentration, improve sensitivity, and reduce surfactant fouling. 443,444,448,449 4.4.2. Electrochemical behavior of GCE modified with ErGO/PEDOT:PSS.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…These properties, along with its low cost compared to other materials, make it a viable option for electrochemical sensors . Earlier efforts for electrochemical detection of 4-NP using graphene-based material as sensors have been made with different nanomaterials. Metal nanoparticles such as gold and silver have been used with reduced graphene oxide (rGO). For example, Tang et al demonstrated a facile method of rGO and gold nanocomposite fabrication for the electrochemical detection of 4-NP .…”
Section: Introductionmentioning
confidence: 99%